EKSTRAKSI MERKURI DARI LIMBAH PENGOLAHAN BIJIH EMAS MENGGUNAKAN TANAMAN AKAR WANGI (Vetiveria zizanioides L.) DENGAN PENAMBAHAN EDTA DAN KOMPOS - Muhammad Kresna Putra; S Syekhfani; Novalia Kusumarini (Jurnal Tanah dan Sumberdaya Lahan, 2018)
One of mining activities in Sukabumi and Bogor is gold mining. This activity uses mercury amalgamation techniques that generate tailings containing mercury. The tailing that is commonly dischared to the environment can affect human healths. One method to solve this problem is phytoremediation. Vetiveria zizanioides L. is one of the hyperaccumulator plants that can uptake mercury. This study was aimed to explore the effects of application of Ethylene Diamine Tetraacetic Acid (EDTA) and compost on uptake of merkuri Vetiveria zizanioides L. Nine treatments (combination of EDTA and compost doses) were tested in his study. Results of the study showed that the combination of compost and EDTA increased the uptake of mercury by Vetiveria zizanioides. Addition of EDTA increased 178% of mercury uptake. Application of compost was able to increase mercury concentration in root by 108% and in canopy by 165%, and increased soil pH, and cation exchange capacity.